Prolonged but not short-duration blast waves elicit acute inflammation in a rodent model of primary blast limb trauma. Issue 3 (March 2016) - Eftaxiopoulou, Theofano; Barnett-Vanes, Ashton; Arora, Hari; Macdonald, Warren; Nguyen, Thuy-Tien N.; Itadani, Mako; Sharrock, Anna E.; Britzman, David; Proud, William G.; Bull, Anthony M.J.; Rankin, Sara M.
Abstract: Background: Blast injuries from conventional and improvised explosive devices account for 75% of injuries from current conflicts; over 70% of injuries involve the limbs. Variable duration and magnitude of blast wave loading occurs in real-life explosions and is hypothesised to cause different injuries. While a number of in vivo models report the inflammatory response to blast injuries, the extent of this response has not been investigated with respect to the duration of the primary blast wave. The relevance is that explosions in open air are of short duration compared to those in confined spaces. Methods: Hindlimbs of adult Sprauge-Dawley rats were subjected to focal isolated primary blast waves of varying overpressure (1.8–3.65 kPa) and duration (3.0–11.5 ms), utilising a shock tube and purpose-built experimental rig. Rats were monitored during and after the blast. At 6 and 24 h after exposure, blood, lungs, liver and muscle tissues were collected and prepared for histology and flow cytometry. Results: At 6 h, increases in circulating neutrophils and CD43Lo/His48Hi monocytes were observed in rats subjected to longer-duration blast waves. This was accompanied by increases in circulating pro-inflammatory chemo/cytokines KC and IL-6. No changes were observed with shorter-duration blast waves irrespective of overpressure. In all cases, no histological damage was observed in muscle, lung or liver. By 24 h post-blast, all inflammatory parameters had normalised. Conclusions: We report the development of a rodent model of primary blast limb trauma that is the first to highlight an important role played by blast wave duration and magnitude in initiating acute inflammatory response following limb injury in the absence of limb fracture or penetrating trauma. The combined biological and mechanical method developed can be used to further understand the complex effects of blast waves in a range of different tissues and organs in vivo .